1989
DOI: 10.1620/tjem.157.221
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiovascular depressant action of clonidine by pentobarbital anesthesia in rats.

Abstract: The influence of pentobarbital anesthesia (5 mg 100 g, i.p.) on the cardiovascular depressor effect of clonidine administered intracerebroventricularly (i.c.v.) and intravenously (i.v.) was examined in rats. In conscious rats the hypotensive potency of i.v. clonidine [effective dose of clonidine which induced a decrease in blood pressure of 15 mmHg ; ED15 = 7 (pg/kg)] is greater than that of i.c.v. clonidine (ED15 =24.3), while in anesthetized rats that of icy. clonidine (ED15 -0.7 pg/kg) was greater than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…On the other hand, clonidine evoked pressor responses and bradycardia when administered into the central nervous system of ketamine/xylazine-anesthetized rats, reproducing data obtained in studies using conscious normotensive rats [24]. It was previously demonstrated that the hypotensive effect of both i.v.- [37] and i.c.v.-administered [21] clonidine was significantly potentiated by pentobarbital anesthesia in rats, circumventing the previously mentioned vasoconstrictor effect of clonidine. Clonidine has been administered as premedication or during anesthesia in humans, and its use has been associated with multiple benefits, including reduced anesthetic requirement [38] and improved hemodynamic parameters [39].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, clonidine evoked pressor responses and bradycardia when administered into the central nervous system of ketamine/xylazine-anesthetized rats, reproducing data obtained in studies using conscious normotensive rats [24]. It was previously demonstrated that the hypotensive effect of both i.v.- [37] and i.c.v.-administered [21] clonidine was significantly potentiated by pentobarbital anesthesia in rats, circumventing the previously mentioned vasoconstrictor effect of clonidine. Clonidine has been administered as premedication or during anesthesia in humans, and its use has been associated with multiple benefits, including reduced anesthetic requirement [38] and improved hemodynamic parameters [39].…”
Section: Discussionsupporting
confidence: 80%
“…Although multiple studies have reproduced the antihypertensive effect of clonidine, a closed analysis of the literature reveals that such findings are strikingly dependent on experimental conditions. The administration of clonidine using the intracerebral route decreased the blood pressure of both conscious hypertensive [17] and anesthetized animals [18][19][20][21][22]. However, despite its efficacy against hypertension, the i.c.v.…”
Section: Introductionmentioning
confidence: 99%